Text-Bild-Beziehungen am Beispiel des Mediendiskurses über den Ukraine-Konflikt - Mikołajczak, Agnieszka (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
In the present article is ventured an attempt of considering the phenomenon of relations between text and image based on the example of a media discourse concerning the Ukrainian Conflict. Taking into account that the media discourse can be profiled through the language and image combination, linguistic analysis will be focused on the interaction between the language and visual means in multimedia texts.The article gives a short historical – political outline of the Ukrainian Conflict, and then based on the chosen examples from German BILD and Tagesspiegel daily newspapers presents various correlations between language and image.